AKTIVITAS ANTIBAKTERI NANOPARTIKEL KITOSAN DARI LIMBAH CANGKANG RAJUNGAN (Portunus pelagicus) TERHADAP BAKTERI Staphylococcus epidermidis - Fauliya, Fauliya; Yusan, Liza Yudistira (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Staphylococcus epidermidis bacteria are commonly associated with causing acne, which is a type of Gram-positive bacteria. Chitosan nanoparticles have potential as antibacterials that can be developed into alternative therapies. The purpose of this study was to determine chitosan nanoparticles derived from crab shell waste (Portunus pelagicus) in inhibiting Staphylococcus epidermidis bacteria. Disc diffusion is the method used to test antibacterial activity. The concentrations of chitosan nanoparticles used were 400 ppm, 600 ppm and 800 ppm. Tetracycline was used as positive control and 1% acetic acid as negative control. The results showed that chitosan nanoparticles had stronger antibacterial activity with increasing concentration, the strongest inhibition at a concentration of 800 ppm (14.12 ± 3.72 mm). Chitosan nanoparticles have antibacterial activity against Saphylococcus epidemidis bacteria. The higher the concentration of chitosan nanoparticles can increase its ability to inhibit bacterial growth.